Glucocorticoid‐induced hyperglycaemia in respiratory disease: a systematic review and meta‐analysis. Issue 12 (4th August 2016) - Breakey, S.; Sharp, S. J.; Adler, A. I.; Challis, B. G.
Abstract : The relative risk of glucocorticoid‐induced hyperglycaemia is poorly quantified. We undertook a meta‐analysis to estimate the association between glucocorticoid treatment and hyperglycaemia, overall and separately in individuals with and without diabetes and underlying respiratory disease. We searched electronic databases for clinical trials of adults randomized to either glucocorticoid treatment or placebo. Eight articles comprising 2121 participants were identified. We performed a random effects meta‐analysis to determine relative risks for the associations between glucocorticoid use and both hyperglycaemia and starting hypoglycaemic therapy. In all individuals, the relative risk of hyperglycaemia comparing glucocorticoid treatment with placebo was 1.72 [95% confidence interval (CI) 1.50‐2.04; p < .001]. The relative risks in individuals with and those without diabetes were 2.10 (95% CI 0.92‐5.02; p = .079) and 1.50 (95% CI 0.79‐2.86; p = .22), respectively. In all individuals, the relative risk of hyperglycaemia requiring initiation of hypoglycaemic therapy, comparing glucocorticoid treatment with placebo, was 1.73 (95% CI 1.40‐2.14; p < .001). In conclusion, glucocorticoid therapy increases the risk of hyperglycaemia in all individuals with underlying respiratory disease but not when diabetic status is analysed separately.